Literature of the management of physical education based on the Scopus database: A bibliometric review - Feby Elra Perdima; Muhammad Kristiawan; Davi Sofyan; Nagoor Meera Abdullah; Nurhuda (Journal Sport Area, 2022)
Effective management is required to aid students in positively developing their character and skills during the physical education learning process. The goal of this study is to conduct a bibliometric analysis of management in physical education publications that have been published in Scopus. The study focuses on the productivity of publishing management in physical education papers on Scopus, on the most prestigious journals, authors, and articles, and on an analysis of keywords that frequently appear in management in physical education articles published on Scopus. The search yields 598 documents that were published in the Scopus database between 2017 and 2021. The majority of publications are written by Webster, C.A., who has six published articles. The most active scientific journal is the Journal of Physical Education and Sport, which has 26 published articles. With 41 links, the United States has the most total link strength of any nation. With 122 instances, "physical education" is the term that is used most frequently. The newest keywords include "big data," "COVID-19," "diet," "sports management," and "knowledge." The most read article on the subject of management in physical education was "Domain-Specific Physical Activity and Mental Health: A Meta-analysis." The research's limitation is that the author is only able to use data from the Scopus database and is only able to use sources that are journal articles; however, the Scopus database also contains other types of sources, including proceedings, book chapters, editorials, notes, erratums, books, and book series. This study contributes to the development of new concepts in the study of physical education management, and it is necessary to conduct future research related to this research theme, which is one of the areas that can be studied more deeply in order to produce learning products according to the needs and developments of the times.